SIFAT FISIKOKIMIA DAN SENSORIS SOHUN INSTAN DARI PATI SAGU - Abdul Rahim; Mappiratu Mappiratu; Amalia Noviyanty (Agroland: Jurnal Ilmu-ilmu Pertanian, 2009)
The objectives of the research was to determine a method for making instant sohun from sago starch that has physicochemical and sensory properties of good quality. Optimizing instant sohun process was achieved by applying four different ratios of sago starch : hot water suspension (v/v) (1:0.75; 1:1; 1:1.25; and 1:1.5) and three different levels of cooking time (4, 6, and 8 minutes).             A Completely Randomized design was used for observing the physicochemical properties, water content, cooking rate and cooking loss, while a Randomized Block design for the sensory properties. The research results showed that the sago starch:hot water suspension at a ratio 1: 0,75 (v/v) and           4 minutes cooking time was the best processing condition for making sohun instant from sago starch in which water content was 10.95%, cooking rate was 3.29 minute and cooking loss was 2.13%. While cooking time for 4 minutes resulted in better sensory properties than any other cooking time.